Ta’ṡīr al-Kafā’at Fī al-Insyā ‘ala al-Kafā’at Fī al-Muhādaṡat al-Yaumiyyat li Ṭullāb al-Fashl al-Ṡāliṡ bi Kulliyyat al-Mu’allimīn al-Islāmiyyat bi Ma’had Dār al-Salām Gontor al-Ḥaram al-Markaziy - Muhammad Abi Abdillah; Rahmat Hidayat Lubis (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2022)
This study aims to examine the effect of Insha' competence on daily conversation competence of 3rd grade students of KMI Gontor Ponorogo. The type of research is descriptive quantitative research (Experimental Study) with a population of 442 students, and a sample of 116 students. The researcher used the well-known Statistical Analysis Method, Product Moment to analyze the data at a significance level of 5% and 114 degrees of freedom. The results of this study are: First, the average score for insya’ lesson test of the third grade students of KMI Darussalam Gontor Islamic Institution Central Campus is 6.1. Second, there is an effect between insya' lesson on the muhadatsah ability of third grade students of KMI Darussalam Gontor Islamic Institution Central Campus and the effect is strong. This can be seen from the results of the calculation of rxy = (0.452) which is greater than the value of "r" Product Moment with the meaning of 5% is: (0.1824), the results of each are as follows: The average score for insya’ lesson of the third grade students of KMI Darussalam Gontor Islamic Institution Central Campus is 6.1. The average score for muhadatsah test of the third grade students of KMI Darussalam Gontor Islamic Institution Central Campus is 6.3. ملخص والهدف من هذا البحث لاختبار تأثير الكفاءة في الانشاء على الكفاءة في المحادثة اليومية لطلاب الفصل الثالث بكلية المعلمين الإسلامية بمعهد دار السلام كونتور الحرم المركزي. ونوع البحث الذي أخذه الباحث هو البحث الميداني الوصفي الكمي (Experimental Research)، وعدد السكان 442 طالبا، وعدد العينة 116 طالبا. واستخدم الباحث في تحليل بطريقة التحليل الإحصائيّ (Statistical Analysis Method)، وذلك من نوعها المشهور الإنتاج اللحظيّ (Product Moment) على مستوى المعنى 5% وبالدرجة الحرية 114. ونتائج هذا البحث هي: أولا، كانت نتيجة الإنشاء للطلاب حصلت على الدرجة المتوسطة حيث وصلت على النتيجة 6,1. وثانيا، يوجد تأثير مادة الإنشاء على الكفاءة في المحادثة اليومية للطلاّب بالتأثير قوي. وذلك يظهر من نتيجة الحساب rxy = (0,452) أكبر من القيمة “r” Product Momentبالمغزى 5% هي: (0,1824)، ونتيجة كل منهما كما يلي: كانت نتيجة الإنشاء للطلاب حصلت على الدرجة المتوسطة بنتيجة 6,1. وكانت النتيجة للمحادثة للطلاب حصلت على الدرجة المتوسطة فهي بنتيجة 6,3.